Challenging some assumptions about empathy. (2nd February 2017) - Gallagher, Peter; Moriarty, Helen; Huthwaite, Mark; Lim, Bee
Summary: Background: In New Zealand little nursing or medical curricula time, if any, is specifically devoted to the enhancement of empathy. If being empathic is important in the context of patient care, it is a quality that is already present in students or is learned by students during their practicum in the company of experienced clinicians. This study aimed to compare self‐reported empathy ratings between different groups of medical students and one cohort of nursing students who were either exposed or not exposed to explicit empathy training or learning in clinical settings in the presence of patients. Methods: The Jefferson Scale of Physician Empathy (JSPE) was completed before and after groups of medical and nursing students had been exposed to various extended periods of practicum. Some medical student cohorts undertook brief empathy training, whereas others had no exposure. The nursing student cohort had no formal, explicit empathy training. Results: Irrespective of profession, length of practicum or exposure to specific empathy training, there were no significant differences in the self‐reported JSPE scores across the seven different cohorts of students. Empathy is a quality that is already present in students or is learned by students during their practicum Discussion: If empathy is caught rather than taught, then brief efforts to enhance empathy may be futile. To optimise the inherent empathic qualities of aspirant health professionals, explicit consideration should be given to how empathy is influenced by the practicum experience.